2007
DOI: 10.1128/jvi.00710-07
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Silver-Haired Bat Rabies Virus Infection Can Be Prevented by Opening the Blood-Brain Barrier

Abstract: Silver-haired bat rabies virus (SHBRV) infection induces a strong virus-specific immune response in the periphery of the host, but death is common due to the failure to open the blood-brain barrier (BBB) and deliver immune effectors to central nervous system (CNS) tissues. Mice with an SJL background are less susceptible to lethal infection with rabies viruses. In addition, these animals are known to have reduced hypothalamuspituitary-adrenal (HPA) axis activity and an elevated capacity to mediate CNS inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
75
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 29 publications
1
75
1
Order By: Relevance
“…Different mechanisms have been proposed to explain the inefficiency of the immune response against RABV infection (24). RABV infection induces immune unresponsiveness (6, 53), limits T cell infiltration into the NS (44), and keeps the blood-brain barrier tightly closed (37,45). It also promotes the destruction of migratory CD8 ϩ T cells in the NS through the upregulation of immunoevasive proteins such as B7-H1 (1, 27, 28).…”
Section: T Cells and Less Disappearance Of Infiltrating Cd8 ؉ T Cellsmentioning
confidence: 99%
“…Different mechanisms have been proposed to explain the inefficiency of the immune response against RABV infection (24). RABV infection induces immune unresponsiveness (6, 53), limits T cell infiltration into the NS (44), and keeps the blood-brain barrier tightly closed (37,45). It also promotes the destruction of migratory CD8 ϩ T cells in the NS through the upregulation of immunoevasive proteins such as B7-H1 (1, 27, 28).…”
Section: T Cells and Less Disappearance Of Infiltrating Cd8 ؉ T Cellsmentioning
confidence: 99%
“…Due to such cases and to research using animal models of RABV infection (6)(7)(8), many believe that the immune system may be capable of clearing RABV from the brain without causing irreparable immunopathology. It is clear, however, that therapeutic intervention will be necessary in the vast majority of cases.…”
mentioning
confidence: 99%
“…Generally, BBB integrity is compromised during infection, and this BBB disruption dictates the aforementioned alterations and brain injury in several neurotropic viruses (3)(4)(5)(6). Though most studies demonstrated the detrimental consequences of BBB breakdown during neurotropic virus infection, the opening of the BBB also prevents certain lethal viral CNS infections (7).…”
mentioning
confidence: 99%